Diplomatic Representation of Lithuania in France in the 1970. The Crisis - Jonušauskas, Laurynas (Genocidas ir rezistencija, 2001)
The author investigates inner disagreements between the chief of Diplomatic Service Stasys Lozoraitis, and Prof. Jurgis Baltrušaitis and Antanas Liutkus, regarding the issues of Lithuania’s representation in France. The crisis was solved with the interference of the USA State Department and official authorities of France. It proves that the Lithuanian Diplomatic Service functioning under conditions of exodus was not completely independent structure able to solve its problems, and that the service was to a great extent dependent on the external factors, especially on the USA, which controlled the finances of the Lithuanian Diplomatic Service.